"Post-conflict Curating": The Arts and Politics of Belfast's Peace Walls. Issue 2 (4th May 2019) - Kappler, Stefanie; McKane, Antoinette
ABSTRACT: This article conceptualises the challenges that curators of the visual arts working in post-conflict contexts face in terms of doing justice to the competing narratives and representations of past violence. To do so, the article first proposes the concept of the city-as-museum, in which independent artists and residential communities may act as curators as much as museum professionals and state organisations do. Against this background, the article goes on to consider the particular curatorial issues presented by the context of "dark tourism" in places like Northern Ireland, where social conflict itself has become the subject of exhibition. We then zoom in on three Loyalist peace walls in Belfast to suggest that those walls have been curated to represent a particular vision of a post-conflict society. We examine recent developments in mural production that have emerged alongside the site's popularity as a "pleasurable" experience for visitors to the city. We suggest that this tension between the Troubles and the visitor's experience generates a discourse on its own that is translated in the kind of wall monument that is created. In that sense, we can, for instance, view the murals in Belfast as sites of creative art on the one hand, and as political visions of the future of the city and region on the other hand. We cast light on the continued significance of the murals as expressions of community identities, and examine their ability to promote narratives of both division and tolerance between communities in the post-conflict city.